PROFESIONALISME PENDIDIK BIOLOGI DALAM MENINGKATKAN MUTU PEMBELAJARAN SAINS DI SMAN 8 KOTA SERANG - Ina Chandra Rosalianti; Pitri Aisyatun Nurul Aeni; Yayah Amaliyah; Maya Rahayu; Amanda Deliana Rahayu (Universitas Cokroaminoto Palopo, 2026)
This study aims to describe the understanding and application of biology teacher professionalism in an effort to improve science learning at SMAN 8, Serang City. A descriptive qualitative research method was used, with data collected through semi-structured interviews and documentation with experienced biology teachers. The results indicate that biology teachers have met high professional and pedagogical competencies, implemented a scientific inquiry-based learning model with supporting media and assessments, and continue to develop themselves through training and educational research. The main obstacles encountered include limited laboratory facilities and lack of student concentration, which were addressed through interactive learning methods. Teacher professionalism significantly contributes to increasing learning interest, conceptual understanding, and the quality of science learning at SMAN 8, Serang City